Surgical Performance Determines Functional Outcome Benefit in the Minimally Invasive Surgery Plus Recombinant Tissue Plasminogen Activator for Intracerebral Hemorrhage Evacuation (MISTIE) Procedure. Issue 6 (20th March 2019) - Awad, Issam A; Polster, Sean P; Carrión-Penagos, Julián; Thompson, Richard E; Cao, Ying; Stadnik, Agnieszka; Money, Patricia Lynn; Fam, Maged D; Koskimäki, Janne; Girard, Romuald; Lane, Karen; McBee, Nichol; et al.
Abstract: BACKGROUND: Minimally invasive surgery procedures, including stereotactic catheter aspiration and clearance of intracerebral hemorrhage (ICH) with recombinant tissue plasminogen activator hold a promise to improve outcome of supratentorial brain hemorrhage, a morbid and disabling type of stroke. A recently completed Phase III randomized trial showed improved mortality but was neutral on the primary outcome (modified Rankin scale score 0 to 3 at 1 yr). OBJECTIVE: To assess surgical performance and its impact on the extent of ICH evacuation and functional outcomes. METHODS: Univariate and multivariate models were used to assess the extent of hematoma evacuation efficacy in relation to mRS 0 to 3 outcome and postulated factors related to patient, disease, and protocol adherence in the surgical arm (n = 242) of the MISTIE trial. RESULTS: Greater ICH reduction has a higher likelihood of achieving mRS of 0 to 3 with a minimum evacuation threshold of ≤15 mL end of treatment ICH volume or ≥70% volume reduction when controlling for disease severity factors. Mortality benefit was achieved at ≤30 mL end of treatment ICH volume, or >53% volume reduction. Initial hematoma volume, history of hypertension, irregular-shaped hematoma, number of alteplase doses given, surgical protocol deviations, and catheter manipulation problems were significant factors in failing to achieve ≤15 mL goal evacuation. Greater surgeon/site experiences were associated with avoiding poor hematoma evacuation. CONCLUSION: This is the first surgical trial reporting thresholds for reduction of ICH volume correlating with improved mortality and functional outcomes. To realize the benefit of surgery, protocol objectives, surgeon education, technical enhancements, and case selection should be focused on this goal.